2006
DOI: 10.1111/j.1468-3083.2006.01567.x
|View full text |Cite
|
Sign up to set email alerts
|

Narrowband UVB phototherapy for small plaque parapsoriasis

Abstract: NB-UVB phototherapy has several advantages over treatment with broadband UVB and PUVA. NB-UVB therapy for patients with SPP is an effective, safe and practical alternative treatment modality. Further larger studies with longer follow-up periods are necessary to determine the proper clinical response and long-term complications of NB-UVB therapy in this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 22 publications
1
6
0
1
Order By: Relevance
“…This regimen is used at our Department for several years and treatment results are satisfactory. The same doses were used also in other studies [1]. …”
Section: Methodsmentioning
confidence: 99%
“…This regimen is used at our Department for several years and treatment results are satisfactory. The same doses were used also in other studies [1]. …”
Section: Methodsmentioning
confidence: 99%
“…The use of narrowband ultraviolet B (NB‐UVB) phototherapy with a peak emission wavelength at 311 nm has been used for the treatment of psoriasis and other inflammatory disorders for 20 years 6,7 . Some authors have shown that wavelengths between 310 nm and 315 nm provoke the fewest erythema, while being most effective in clearing psoriasis 8 .…”
Section: Introductionmentioning
confidence: 99%
“…To parapsoriasis en plaques, our result suggested that hydrogen-water bathing was rapidly effective and safe for the control of the disease with 66.7% partial response and 33.3% complete response. Currently, PUVA and narrow-band UVB are used as main treatment options for parapsoriasis en plaques with up to 80% complete remission rates and a median time to clearance of 2–6 months 6 , 28 , 29 . In general, UVB is preferred in patients with patches and thin plaques and PUVA photochemotherapy should be used for patients with thick plaques, with phototypes ≥III and unresponsive to UVB 6 .…”
Section: Discussionmentioning
confidence: 99%